The Relationship Of Mom's Knowledge About Iud With Participation As Iud Accepters In Hana Kasih Clinic In 2019 - Dwi Ris Hasanah S; Arva Rochmawati Rochmawati (Institute of Computer Science (IOCS), 2019)
Contraceptive IUD is a tool or object that is inserted into the uterus which is very effective, reversible and long-term can be used by all women of reproductive age. The purpose of this study was to determine the relationship between mother's knowledge of the IUD and her participation as an IUD acceptor at the Hana Kasih Clinic in 2019. The research method used was analytical observation with a cross sectional approach. The population is all women of childbearing age who visited the Hana Kasih Clinic in 2019, totaling 30 respondents. The sample in this study was some 30 women of childbearing age at the Hana Kasih Clinic in 2019. The results of the analysis showed that the majority of PUS mothers who had good knowledge participated as 9 IUD acceptors (69.3%), 4 people with sufficient knowledge also participated (30,7%). From the results of the Chi-Square statistical test, p = 0.000, which means that there is a relationship between mother's knowledge and participation as an IUD acceptor. It is recommended to health workers to continue to provide counseling about how to use, and the benefits of mother's participation as IUD acceptors.